EPID-12. IMPACT OF RACE AND GEOGRAPHIC LOCATION ON IDH MUTATIONS AND GLIOBLASTOMA SURVIVAL. (11th November 2019) - McCormack, Ryan; Zhu, Ping; Takayasu, Takeshi; Hines, Gabriella; Zeineddine, Hussein; Tandon, Nitin; Moreno Jimenez, Sergio; Gonzalez, Alberto; Ballester, Leomar Y; Esquenazi, Yoshua
Abstract: Glioblastoma (GBM) is the most common primary malignant brain tumor of the central nervous system with a 5-year survival of < 5%. Population studies have demonstrated that among all ethnicities, non-Hispanic whites (NHW) have the worst prognosis; however, differences within the oncogenome based on ethnicity have not been assessed. We utilized the Texas Cancer Registry (TCR) for population-based analysis including 4, 134 GBM patients between the years of 1995 to 2013 with 75.6% NHW and 16.5% Hispanics. In accordance with previously published findings, within the TCR we detected a 12% relative survival improvement in Hispanics compared to NHW when controlling for known survival mediators including age, resection, chemotherapy, and radiation. In order to assess for oncogenic differences, we utilized a prospectively maintained database of 257 GBM patients within the city of Houston, TX (14.9% Hispanic) and 48 GBM patients from the National Institute of Neurology and Neurosurgery in Mexico City, Mexico (100% Hispanic) to assess for oncogenomic differences attributable to ethnicity. Next generation sequencing of GBM within the Houston cohort, for 315 tumor-related genes, identified no significant differences in genomic alterations owing to ethnicity. However, when we compared the multigenerational, mixed-heritage Hispanics present in the Houston cohort to the Mexico cohort (Sanger sequencing), a significant difference was found in the frequency of IDH1and IDH2mutations (29.8 % Mexico Hispanics, 7.9% Houston Hispanics; p=0.014). In particular, the rate of IDH2mutations is significantly enriched in the Mexico population (19%) when compared to the Houston population (0%) or to previously published rates of IDH2 mutations in GBM (~3%). Ultimately, these findings highlight the need for multiethnic trial enrollment as well as the need for improved testing of IDH2 mutations in patients of distinct ethnicities. Future studies are needed to identify the mechanisms promoting the increased frequency of IDH2 mutations in Mexican Hispanics.